Comparing the market history of mobile phones and electric cars by using sigmoid curves - Szabó, Ferenc János (Design of Machines and Structures, 2024)
The time curves of market history for mobile phones and for electric cars is compared by sigmoid curves. Creating the approximate sigmoid curves of the curves showing the real data of products sold in function of the time, it is possible to find similarities and differences of the time history of the market of mobile phones and electric cars. One of the most important decisions during this investigation is to decide, which curve describes better the product investigated: Logistic curve (Pearl-Reed curve) or Growth curve (Bertalanffy)? On the basis of many characteristics of these curves, in the second step of the study it is possible to characterise the market of the products, and the comparison can give important points of view for the understanding the present situation of the markets and to try to forecast their possible future.